1977
DOI: 10.1093/jnci/58.2.189
|View full text |Cite
|
Sign up to set email alerts
|

IgG4 Subclass in Malignant Melanoma

Abstract: Three hundred and ninety-seven sera from 185 melanoma patients were studied. These sera were classified into three groups according to stage of disease. An alteration in the level of the IgG4 subclass was found. It was related to the dissemination of disease. The percentage of abnormalities (either increased or decreased levels of IgG4) was more frequent in patients with stage II and III diseases (55 and 53%, respectively) than in patients with stage I(19%). The higher frequencies of high titers of IgG4 were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

1982
1982
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 0 publications
0
21
0
1
Order By: Relevance
“…Infiltrating IgG4 + cells in lesions of patients with extrahepatic cholangiocarcinomas and pancreatic cancers were recently reported (19,20), and early studies have indicated abnormalities in serum titers of IgG4 in patients with melanoma (21). Both the presence and potential biological role of IgG4 subclass antibodies in melanoma tumor lesions remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Infiltrating IgG4 + cells in lesions of patients with extrahepatic cholangiocarcinomas and pancreatic cancers were recently reported (19,20), and early studies have indicated abnormalities in serum titers of IgG4 in patients with melanoma (21). Both the presence and potential biological role of IgG4 subclass antibodies in melanoma tumor lesions remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, the relationship between IgG4 and malignancy remains largely unexplored, although IgG4+ cells were reported to infiltrate extrahepatic cholangiocarcinomas and pancreatic cancers [25]. Abnormal serum titers of IgG4 have been observed in patients with melanoma [26], and IgG4 was recently reported to significantly impair the potency of tumoricidal IgG1 in a human melanoma xenograft mouse model [17]. Serum IgG4 was shown to correlate inversely with survival in patients with melanoma [17].…”
Section: Introductionmentioning
confidence: 99%
“…Three decades ago, Daveau and colleagues reported altered levels of IgG4 antibodies in the serum of melanoma patients 7 . Although this indicated that B cells in melanoma patients undergo antibody class/subclass switching, the underlying mechanisms and significance remained unexplored.…”
mentioning
confidence: 99%